ANALISIS PENGARUH BAURAN PROMOSI TERHADAP VOLUME PENJUALAN KONDOMINIUM DI KAWASAN KOTA SURABAYA - Sumitro, Yanus; Helmy, Bachtiar J; Soekotjo, Wahjono (Majalah Ekonomi, 2019)
Purpose of this study was to analyze the promotion mix (advertising, sales promotion, publicity and personal selling) simultaneously and partially on the volume of home sales in Surabaya Wiguna Areas and to analyze the promotional mix that has a dominant influence on the volume of home sales in the Surabaya Wiguna Area. The results showed that the promotion mix (advertising, sales promotion, publicity and personal selling) simultaneously significant effect on home sales in the Surabaya Wiguna Area. While the promotion mix (advertising, sales promotion, publicity and personal selling) is partially significant effect on home sales, because there are three independent variables were not significant variables are advertising, sales promotion, and personal selling. While publicity is the dominant variable affecting home sales.